2020
DOI: 10.35848/1882-0786/aba7a6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced luminescence of solid blue carbon dots by the “Islands” Ag films for highly efficient light-emitting diodes

Abstract: The photoluminescent of carbon dots (CDs) was significantly quenched when CDs were densely deposited on glass substrates, which limited their applications. In this work, the luminescent enhancement of blue CDs with polymer of polyvinylpyrrolidone (PVP) is explored by coupling with an "Island" Ag film. The fluorescence intensity of CDs enhances nearly 5-fold. Furthermore, the application of Ag/CDs/PVP in LEDs was explored, the luminous efficiency is up to 39.2 lm W −1 . After 10 h of continuous operation, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Better results are achieved by exploiting the surface plasmonic resonance of an “islands” Ag film coupled with a blue CDs/PVP solid film. Here, the stability increases by a factor of 10, with reference to the previous orange-emitting CD case: the emission intensity decreased by about 5% after 10 h under continuous operation [ 139 ].…”
Section: Color Conversion Cd-based Ledsmentioning
confidence: 89%
See 1 more Smart Citation
“…Better results are achieved by exploiting the surface plasmonic resonance of an “islands” Ag film coupled with a blue CDs/PVP solid film. Here, the stability increases by a factor of 10, with reference to the previous orange-emitting CD case: the emission intensity decreased by about 5% after 10 h under continuous operation [ 139 ].…”
Section: Color Conversion Cd-based Ledsmentioning
confidence: 89%
“…It has been demonstrated that the luminous intensity of CDs can be increased by a factor of three [ 138 ]. Cui et al proved a further improvement by a factor of five by coupling blue CDs (embedded in PVP) with an Ag film made of surface plasmonic resonance “islands” [ 139 ].…”
Section: Color Conversion Cd-based Ledsmentioning
confidence: 99%